1987
DOI: 10.1021/jo00377a005
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective ring construction: synthesis of (+)-estrone methyl ether

Abstract: m/e (M+) 273.0993 (caled for C15H16N04 273.1001). 6-(Aminocarbonyl)-7,8-dihydro-6H-furo[3,2-e]indole-2carboxylic Acid (7). A suspension of 35b (0.27 g, 1.0 mmol) in methanol (15 mL) was basified with 0.1 N NaOH to pH 10 and was stirred until starting material was consumed as indicated by TLC. The solution was acidified with 0.1 N HC1 to pH 1 and chilled, and the solid was filtered and dried over P205 to yield acid 7 [0.20 g (80%)] as an off-white solid: dec pt >230 °C; lH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
0
21
0
Order By: Relevance
“…365 Highly diastereoselective insertions were also described for reactions employing enantiomerically pure β-ketoesters 369,370 and β-ketoesters with chiral auxiliaries. 367, 368 A common side reaction in C−H insertion processes is β-hydride elimination, and it has been demonstrated that the use of Rh 2 (tfa) 4 can encourage this pathway, leading to a useful synthesis of Z-α,β-unsaturated ketones and esters. 373 Since Taber and co-workers have also shown that, in favorable cases, α-aryldiazoketones will cyclize to form cyclohexanones in preference to cyclopentanones, due to the more electronically discriminating nature of the derived metal carbenes, when compared with carbenes derived from α-diazoesters (Scheme 145).…”
Section: Catalytic Asymmetric C−h Insertion Reactionsmentioning
confidence: 99%
“…365 Highly diastereoselective insertions were also described for reactions employing enantiomerically pure β-ketoesters 369,370 and β-ketoesters with chiral auxiliaries. 367, 368 A common side reaction in C−H insertion processes is β-hydride elimination, and it has been demonstrated that the use of Rh 2 (tfa) 4 can encourage this pathway, leading to a useful synthesis of Z-α,β-unsaturated ketones and esters. 373 Since Taber and co-workers have also shown that, in favorable cases, α-aryldiazoketones will cyclize to form cyclohexanones in preference to cyclopentanones, due to the more electronically discriminating nature of the derived metal carbenes, when compared with carbenes derived from α-diazoesters (Scheme 145).…”
Section: Catalytic Asymmetric C−h Insertion Reactionsmentioning
confidence: 99%
“…[11] The synthesis of ()-estrone methyl ether (27) illustrates the enantioselective construction of a polycyclic target using chiral auxiliary control to establish the first cyclic stereogenic center. [12] The specific design of the naphthyl diazoester 23 directs Rh-mediated intramolecular C ± H insertion selectively toward one of the two diastereotopic C ± H bonds on the target methylene. The new ternary center so created then directs the formation of the adjacent quaternary center in the course of the alkylation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have speculated that the ester carbonyl and the rhodium carbenoid could be either syn, anti or orthogonal [10 a, d, 17, 18], but no experimental or computational evidence in favor of any of these had been put forward. Since our computational approach did not allow us to answer this question directly, we devised an indirect approach based on the cyclization of a-diazoester 27, derived from the naphthylborneol 31 [19].…”
Section: Chiral Auxiliary Controlmentioning
confidence: 99%